1990
DOI: 10.1021/bi00480a025
|View full text |Cite
|
Sign up to set email alerts
|

Purification and reconstitution of the sodium- and potassium-coupled glutamate transport glycoprotein from rat brain

Abstract: The sodium- and potassium-coupled L-glutamate transporter from rat brain has been purified to near homogeneity by reconstitution of transport as an assay, assuming that inactivated and active transporters cochromatograph. The purification steps involve lectin chromatography of the membrane proteins solubilized with 3-[(3-chloramidopropyl)dimethylammonio]-1-propanesulfonate (CHAPS), fractionation on hydroxylapatite, and ion-exchange chromatography. The specific activity is increased 30-fold. The actual purifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(137 citation statements)
references
References 34 publications
(44 reference statements)
4
133
0
Order By: Relevance
“…Recently, it has been shown that this family also encodes sodium-dependent transporters that do not use dicarboxylic acids as substrates, but rather neutral amino acids (Shafqat et al 1993;Arriza et al 1993). GLT-1, which encodes the glutamate transporter that was purified (Pines et al 1992;Danbolt et al 1990Danbolt et al , 1992, has 573 amino acids and a molecular mass of 64 kDa, in good agreement with the value of 65 kDa of the purified and deglycosylated transporter . Hydropathy plots are relatively straightforward at the aminoterminal side of the protein and the three different groups have predicted six transmembrane ␣-helices at very similar positions (Storck et al 1992;Pines et al 1992;Kanai and Hediger, 1992).…”
Section: Molecular Cloning and Predicted Structure Of Glutamate Transsupporting
confidence: 58%
See 2 more Smart Citations
“…Recently, it has been shown that this family also encodes sodium-dependent transporters that do not use dicarboxylic acids as substrates, but rather neutral amino acids (Shafqat et al 1993;Arriza et al 1993). GLT-1, which encodes the glutamate transporter that was purified (Pines et al 1992;Danbolt et al 1990Danbolt et al , 1992, has 573 amino acids and a molecular mass of 64 kDa, in good agreement with the value of 65 kDa of the purified and deglycosylated transporter . Hydropathy plots are relatively straightforward at the aminoterminal side of the protein and the three different groups have predicted six transmembrane ␣-helices at very similar positions (Storck et al 1992;Pines et al 1992;Kanai and Hediger, 1992).…”
Section: Molecular Cloning and Predicted Structure Of Glutamate Transsupporting
confidence: 58%
“…Using methodology that enables one to reconstitute many samples simultaneously and rapidly, one of each of the subtypes of the GABA (Radian et al 1986) and the Lglutamate (Danbolt et al 1990) transporters have been purified to apparent homogeneity. Both are glycoproteins and both have an apparent molecular mass of 70-80 kDa.…”
Section: Reconstitution Purification and Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…and decapitated; the brains were dissected and the frontal cortex, hippocampus, and striatum were removed. Homogenization and crude synaptic plasma membrane preparation were carried out as described previously (Danbolt et al, 1990). Bio-Rad Protein Assay (Bio-Rad Laboratories, GmbH, München, Germany) and a Beckman DU 530 spectrophotometer (Beckman Coulter, Fullerton, CA, USA) were used to determine the total amount of protein in each homogenate (3-4 measurements per homogenate).…”
Section: Western Blottingmentioning
confidence: 99%
“…The Na+-dependent, high affinity glutamate transporters known so far show complex expression patterns in neuronal and glial cells as well as in different regions of central nervous system [1,33,34]. Therefore an understanding of the association of neurodegenerative disorders of excitatory neurons with glutamate transporter mutations on the molecular level is pivotally associated with the knowledge of the gene structure and chromosome localization of all glutamate neurotransmitter transporters known so far.…”
Section: Assignment Of Hglast-1 Locus To Chromosome 5pll-p12mentioning
confidence: 99%